High Hypoxia Inducible Factor-1α Expression and Positive Limphovascular Invasion as Risk Factors for Axillary Lymph Nodes Metastasis in Breast Cancer - Setiawan, I Gede Budhi; Suanjaya, Made Agus; Suryawisesa, IB Made (Indonesian Journal of Cancer, 2025)
Background: Hypoxia-inducible factor-1α (HIF-1α) expression enables tumor cell proliferation and has a role in the processes of epithelial-mesenchymal transition, invasion, extravasation, and metastasis. Lymphovascular Invasion (LVI) causes a significant increase in the occurrence of axilla lymph node metastasis. This study aims to prove that high HIF-1α expression and LVI (+) as risk factors for axillary lymph node metastasis in breast cancer. Method: The study conducted was a case-control study involving all histopathologically confirmed breast cancer patients at Prof. Dr. I.G.N.G. Ngoerah Hospital during the period from January 2019 to December 2022. In this study, the case group consisted of patients with breast cancer and axilla lymph node (+), while the control group included breast cancer patients without these characteristics. Data analysis was processed using SPSS version 26, which included descriptive statistical analysis, proportion comparison tests, and multiple logistic regression tests, with significance set at p 0.05.Results: LVI (+) has a risk of metastasis to lymph nodes (+) of 6 times (95% CI 1.53–23.44, P = 0.007) and adjusted OR 4.33 (95% CI 2.369–6.053; P = 0.025). The results of the HIF1-α ROC curve obtained a sensitivity value of 86.4% and specificity of 79.2% with a cut-off value of 5.4. A score ≥ 5.4 has a risk of metastasis to lymph nodes (+) of 24.01 times (95% CI 5.03–115.25; P 0.001) and adjusted OR 24.06 (95% CI 5.026–115.247; p 0.001). Conclusion: High HIF-1α expression and positive lymphovascular invasion as risk factors for axillary lymph node metastasis in breast cancer, with HIF-1α showing a particularly strong association. These findings suggest their potential as predictive biomarkers for metastasis. However, the study’s retrospective, single-center design limits generalizability. Future research should validate these results in larger, multicenter cohorts and explore the underlying mechanism to enhance clinical application.